Acetone: a solvent or a reagent depending on the addition order in SET-LRP. Issue 45 (6th November 2018) - Moreno, Adrian; Lejnieks, Jānis; Galià, Marina; Lligadas, Gerard; Percec, Virgil
Abstract : The importance of reagent order in biphasic SET-LRP in acetone/water mixtures is shown. Abstract : Depending on the order of addition to the reaction mixture during biphasic SET-LRP performed in acetone/water mixtures, acetone can serve as a solvent or as a reagent brominated by CuBr2 to provide the electrophilic bromoacetone initiator as well as aldol condensation products.